Investigating Islamic advertising ethics:perceptions of Indonesian Muslims / Fadhil Akbar Purnama and Anya Safira - Safira, Anya (Faculty of Business and Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
Several studies have found that Muslims have different attitudes towards advertising compared to people of other faiths, which makes Muslims an especially interesting group of consumers to study. This research attempts to contribute to the understanding of Islamic advertising by investigating ethical advertising from the eyes of Indonesian Muslim consumers. More specifically, this study investigates whether there are differing ethical perceptions of advertisements between Indonesian Muslims of different age, gender, ethnicity, and levels of religiosity. Analysis of Variance (ANOVA) and independent sample t-test were used to compare the varying perceptions of the respondents towards the Islamic ethical advertising elements.